Antifungal activity of analogues of antimicrobial peptides isolated from bee venoms against vulvovaginal Candida spp - Kočendová, Jitka; Vaňková, Eva; Volejníková, Andrea; Nešuta, Ondřej; Buděšínský, Miloš; Socha, Ondřej; Hájek, Miroslav; Hadravová, Romana; Čeřovský, Václav (FEMS yeast research, 2019)
Candida albicans is the main causative agent of vulvovaginal candidiasis (VVC), a common mycosis in women, relapses of which are difficult to manage due to biofilm formation. This study aimed at developing novel non-toxic compounds active against Candida spp. biofilms. We synthesised analogues of natural antifungal peptides LL-III (LL-III/43) and HAL-2 (peptide VIII) originally isolated from bee venoms and elucidated their structures by nuclear magnetic resonance spectroscopy. The haemolytic, cytotoxic, antifungal and anti-biofilm activities of LL-III/43 and peptide VIII were then tested. LL-III/43 and VIII showed moderate cytotoxicity to HUVEC-2 cells and had comparable inhibitory activity against C. albicans and non-albicans spp. The lowest minimum inhibitory concentration (MIC90) of LL-III/43 was observed towards Candida tropicalis (0.8 µM). That was 8-fold lower than that of antimycotic amphotericin B. Both peptides can be used to inhibit Candida spp. bio film f ormation. Biofilm inhibitory concentrations (BIC50) ranged from 0.9 to 58.6 µM and biofilm eradication concentrations (BEC50) for almost all tested Candida spp. strains ranged from 12.8 to 200 µM. Als o pro ven were the peptides' abilities to reduce the area colonised by biofilms , inhibit hyphae formation and permeabilise cell membranes in biofil ms . LL-III/43 and VIII are promising candidates for further development as therapeutics against VVC.
Keywords: kationické antimikrobiální peptidy; Microbial Sensitivity Tests; biofilm eradication; biofilm inhibition; Candidiasis, Vulvovaginal; vulvovaginal candidiasis; Humans; antifungal peptides; antifungální látky; Amphotericin B; Female; Bee Venoms; Hyphae; mikrobiální testy citlivosti; Candida tropicalis; lidé; Cells, Cultured; amfotericin B; Human Umbilical Vein Endothelial Cells; Antimicrobial Cationic Peptides; kandidóza vulvovaginální; hyfy; ženské pohlaví; biofilmy; Antifungal Agents; kultivované buňky; endoteliální buňky pupečníkové žíly (lidské); Candida albicans; včelí jedy; Biofilms; Candida